Copper-Catalyzed Direct C-5 Fluorination of 8-Aminoquinolines by Remote C–H Activation - Luo, Si-Si; Su, Lan-Jun; Jiang, Yue; Li, Xiao-Bao; Li, Zheng-Hui; Sun, Huan; Liu, Ji-Kai (Synlett, 2018)
A convenient method was developed for direct regioselective fluorination of 8-aminoquinolines at the C-5 position by copper-catalyzed remote C–H activation using Selectfluor as the electrophile fluorinating reagent. With this method, diverse fluorinated quinoline derivatives were facilely obtained under mild conditions with moderate yields.
Keywords: fluorination; copper-catalyzed; 8-aminoquinolines; Selectfluor; remote C–H activation